The production of construction and demolition waste material and the use of recycled aggregates in Havana, Cuba - Elier Pavón; Miren Etxeberria; Iván Martínez (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
This paper deals with the analysis of the generation of Construction and Demolition Waste (CDW) in Havana, Cuba, for the period 1999 to 2010 and its possible use in the manufacturing of recycled aggregates in mortar and concrete production. In order to define the possible applications of the CDW as aggregates in mortar and concrete production the characteristics of the waste as well as studying the existing technologies available in the province for their treatment were analysed. Based on the experimental results, it was determined that the recycled fine aggregates of a mixed composition achieved the minimum requirements defined by Cuban regulations. All the mortars produced with recycled fine aggregates achieved a compressive strength of 5.2 MPa after 28 days which is the minimum requirement for a Type III mortar, consequently they could be used in the manufacturing of masonry mortar. The recycled coarse aggregate originating from pre-cast floor elements could possibly be used in the production of structural concrete for medium and low aggressive environments when concretes were made with 50% and 100% of recycled coarse aggregates in substitution of the natural aggregates, respectively.